Identifying The Role Of Key Opinion Leaders (KOL) Towards Brand Awareness Through Customer Engagement On The Instagram Miracle Aesthetic Clinic Kuta - Sabrina Sabrina; Erlita Ridanasti (Cita konsultindo, 2024)
This research aims to identify the role of Key Opinion Leaders (KOL) in brand awareness through customer engagement on the Miracle Aesthetic Clinic Kuta Instagram account. Miracle Aesthetic Clinic Kuta is the leading beauty clinic in Indonesia, offering superior service to its consumers. The method used in this research is a qualitative method with observational data collection techniques, in-depth interviews and supported by documentation so that the research becomes more credible. The results of this research explain that the role of KOLs as opinion leaders is considered quite significant in disseminating information through content aimed at attracting a wider range of potential consumers. This is then expected to bring organic customer engagement. Brand awareness can then be obtained by creating positive perceptions about the brand through engagement from consumers.